Spike Timing-Dependent Plasticity in the CA1 Pyramidal Neuron in a Modeled Hippocampal Circuit - Ren, H.X.; Liu, Sh.Q.; Zhang, X.C.; Zeng, Y.J. (Нейрофизиология, 2015)
Spike timing-dependent plasticity (STDP) plays an important role in sculpting informationstoring circuits in the hippocampus, since motor learning and memory are thought to be
closely linked with this classical plasticity. To further understand the information delivery in
a hippocampus circuit, we build a computational model to study the potential role of linear
changes in the synaptic weight and synaptic number. Several key results have been obtained:
(i) Changes in the synaptic weight and numbers lead to different long-term modification; (ii)
the first paired spiking from two neurons significantly influences the adjusted subsequent
paired spiking; the pre-post spiking pair strengthens the following paired spiking; however,
the post-pre spiking pair depresses the subsequent spiking; (iii) when the synaptic weight and
synaptic numbers are changed, the interval of the first spiking pair may undergo reduction,
and (iv) when we stimulate a stellate neuron weakly or decrease the capacitance of CA1
pyramidal neuron, LTP is more easily produced than LTD; on the contrary, LTD is more easily
produced in an opposite situation; increase in the synaptic numbers can promote activation of
the CA1 pyramidal neuron. Пластичність, залежна від часу генерування піків (spike
timing-dependent plasticity – STDP), відіграє важливу роль
у формуванні нейромереж, що накопичують інформацію
в гіпокампі; вважається, що моторне навчання та пам’ять
тісно пов’язані з пластичністю цього типу. Для глибшого
розуміння процесів передачі інформації в гіпокампальній
нейромережі ми створили комп’ютерну модель, щоб
вивчити потенціальну роль лінійних змін синаптичної ваги
та числа синапсів у таких мережах. Було отримано чотири
основні результати: 1) зміни ваги та числа синапсів можуть
призводити до появи різних феноменів довготривалої
модифікації; 2) перша пара потенціалів дії, генерована
двома нейронами, істотно впливає на характеристики другої
пари піків; генерація пари піків у пре-пост-послідовності
полегшує генерацію наступної пари, тоді як пост-прегенерація пари пригнічує генерацію наступної пари; 3) коли
вага синапсів та їх кількість змінюються, інтервал у першій
парі піків зменшується; 4) коли стимулювати зірчастий
нейрон з невеликою інтенсивністю або зменшити ємність
пірамідного нейрона CA1, легше індукується довготривала
потенціація; у протилежній ситуації легше виникає
довготривала депресія; збільшення числа синапсів полегшує
активацію пірамідного нейрона CA1.